Skateboarding and the surplus value of city play - Glenney, Brian; Bjorke, Isaac; Buchetti, Andrea (Frontiers in Sports and Active Living, 2024)
Cities, defined materially by concreted surfaces and geometrically shaped structures, have a novel ecology, a "grey space." Grey spaces are criticized for their lack of salubrity in contrast to blue and green spaces enriched by natural biodiversity. How might cities become salubrious? We consider urban play as a source of surplus value both in the context of capitalist frames of labour vs. leisure and societal frames of obedience vs. deviance. We also discuss how some skate play is more ineffable, such as play that is for its own sake, deep play, edgework, and Promethean play. We explore these various facets of skate play in three spatial settings: 1) City-built skateparks, 2) DIY skateparks, and 3) Street spots. We then consider the more ineffable forms of skate play in the context of a Marxist framework of unalienated labour and argue that its unique reimaging of banal urban architecture: stairs, curbs, ledges, etc. creates a diversity of surplus value in the city. These more ineffable forms of play provide unique potential for human fulfilment and identity creation. Grey spaces can be enriched by social play diversity if cities open spaces for citizens to comfortably and naturally initiate diverse frames of play.